Mickiewiczowska wizja "słowiańskiego kontynentu" = Mickiewicz's vision of a "slavic continent" - Ławski, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses the vision of the place and role of Slavs in culture and civilization - the vision promulgated by the Polish romantic poet Adam Mickiewicz (1798-1855) at College de France in Paris in 1840. From 1840 to 1844, in his capacity as professor of Slavic literatures, he lectured on all Slavic cultures: Western, Eastern and Southern. In his inaugural lecture, drawing on Johann G. Herder's famous theses, Mickiewicz outlined the space inhabited by Slavs: from the Kamchatka Peninsula to the Vistula; from Dubrovnik and Varna to Saint Petersburg.
Keywords: Mickiewicz, Adam (1798-1855); słowianofilstwo